Direct exchange interaction of localized spins associated with unpaired sp electrons in Be-doped low-temperature-grown GaAs layers - Bae, K. W.; Mohamed, Mohd Ambri; Jung, DaeWon; Otsuka, Nobuo (American Institute of Physics, 2011)
Beryllium-doped GaAs layers grown at low temperatures by molecular-beam epitaxy contain localized spins associated with unpaired sp electrons of As Ga + ions. Interactions of these localized spins are investigated by measuring the magnetization with a superconducting quantum interference device and the peak-to-peak width of electron paramagnetic resonance (EPR) spectra for samples with different spin concentrations ranging from 3 10 18 to 2.0 10 19cm -3. The results show that localized spins in this material antiferromagnetically interact on each other via direct exchange. From the analysis of the temperature dependence and field dependence of the magnetization on the basis of the Curie-Weiss law and the molecular-field approximation, exchange energy of each sample was derived. The dependence of the exchange energy on the concentration of localized spins is reasonably explained by a model of direct exchange, which results from the overlapping of wave functions of unpaired electrons at As Ga + ions. The peak-to-peak width of EPR spectra increases with an increase in the spin concentration at low temperatures, whereas it decreases with an increase in the temperature for samples with high spin concentrations. These EPR results also show that significant exchange interactions indeed occur between localized spins in this material. These effects of direct exchange interactions between localized spins can clearly be observed at their average distances of around 4 nm, which implies a considerably large spatial extension of the wave function of an unpaired sp electron around an As Ga + ion.